2020
DOI: 10.3390/ijms21239267
|View full text |Cite
|
Sign up to set email alerts
|

A Topical Formulation of Melatoninergic Compounds Exerts Strong Hypotensive and Neuroprotective Effects in a Rat Model of Hypertensive Glaucoma

Abstract: Melatonin is of great importance for regulating several eye processes, including pressure homeostasis. Melatonin in combination with agomelatine has been recently reported to reduce intraocular pressure (IOP) with higher efficacy than each compound alone. Here, we used the methylcellulose (MCE) rat model of hypertensive glaucoma, an optic neuropathy characterized by the apoptotic death of retinal ganglion cells (RGCs), to evaluate the hypotensive and neuroprotective efficacy of an eye drop nanomicellar formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 76 publications
7
20
0
Order By: Relevance
“…38,39 Previous studies also have revealed that melatonin could promote RGC survival and recover retinal dysfunction in rodent models of chronic ocular hypertensive glaucoma via diverse mechanisms, including reducing IOP and oxidative stress, increasing neurotrophin levels, and alleviating gliosis-related inflammation and Bax-associated apoptosis. [72][73][74] However, the role of melatonin in acute glaucoma is still unknown, and this study could offer a potential therapeutic treatment strategy for acute glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Previous studies also have revealed that melatonin could promote RGC survival and recover retinal dysfunction in rodent models of chronic ocular hypertensive glaucoma via diverse mechanisms, including reducing IOP and oxidative stress, increasing neurotrophin levels, and alleviating gliosis-related inflammation and Bax-associated apoptosis. [72][73][74] However, the role of melatonin in acute glaucoma is still unknown, and this study could offer a potential therapeutic treatment strategy for acute glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have revealed that melatonin participates in the pathophysiological process of glaucoma and owns therapeutic potential at various levels, 66 such as circadian system regulation, 67 antioxidant properties, 19 IOP regulation, 68,69 ocular blood flow regulation, 70 sleep disorder, 71 and depression and anxiety 38,39 . Previous studies also have revealed that melatonin could promote RGC survival and recover retinal dysfunction in rodent models of chronic ocular hypertensive glaucoma via diverse mechanisms, including reducing IOP and oxidative stress, increasing neurotrophin levels, and alleviating gliosis‐related inflammation and Bax‐associated apoptosis 72–74 . However, the role of melatonin in acute glaucoma is still unknown, and this study could offer a potential therapeutic treatment strategy for acute glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the melatonin released from the contact lenses did not penetrate the vitreous body and retina, which would limit the treatment of posterior ocular pathologies and require other therapeutic alternatives, mainly via intravitreal injections [ 28 ]. A recent study in rats performed by Dal Monte et al [ 29 ] demonstrated the poor bioavailability of melatonin in the vitreous body and retina resulting from its topical instillation (lower than 1%).…”
Section: Discussionmentioning
confidence: 99%
“…The slight increase (not statistically significant) in the intraocular pressure exclusively found in the rabbits wearing the contact lenses supports this theory. Moreover, despite the fact that it is logical to think that melatonin bioavailability in the aqueous humor was higher with the contact lenses compared to the topical instillation, as discussed above [ 29 ], it should have been confirmed with a control group that was treated topically with melatonin. The melatonin bioavailability required to reduce the production of aqueous humor and (therefore) the intraocular pressure is unknown, as is whether the use of these contact lenses could interfere.…”
Section: Discussionmentioning
confidence: 99%
“…The latter with properties of short half-life and ultrahigh maximal plasma concentrations may further result in low bioavailability due to the deficient absorption and high risk of tolerability issues ( Seiden and Shah, 2019 ). In the current treatment of ophthalmic diseases, the ocular surface is the most common drug delivery route, and the eye drops have been widely used for delivering melatonin in animal experiments; however, their bioavailability should be further examined owing to the ocular barriers ( Dal Monte et al, 2020 ). For bypassing the barriers, the efficacy of intravitreal injection is also examined, especially in treating retinal diseases; however, the previous study reported that the high-dose melatonin injection resulted in degeneration of retinal cells ( Yilmaz et al, 2004 ; Sande et al, 2014 ; Tao et al, 2020 ).…”
Section: Enhancing the Bioavailabilitymentioning
confidence: 99%